Does user-generated content trigger university graduates’ online purchase intention? Mediating role of brand image - Islam, Md. Ashraful; Kaium, Md. Abdul; Zahan, Ishrat; Rahman, Md. Shahinur (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
Academic interest in understanding the impact of user-generated content (UGC) on consumer behavior in digital marketing has grown exponentially. However, we know little about the effect of UGC on customers’ online purchase intention from developing country aspects. This underpins the current study to examine the impact of UGC on the purchase intentions of university graduates in Bangladesh. With a convenient sampling approach, a structured questionnaire was provided directly to 400 respondents; 275 usable and complete responses were extracted for data analysis. Data were empirically validated using principal component analysis, reliability test, correlation, and Hayes PROCESS macro for regression and simple mediation analysis. The findings revealed that bloggers’ recommendations, online communities, and social media content positively and significantly influence customers’ online purchase intention. Brand image also directly impacts purchase intention and mediates the relationship between bloggers’ recommendations, online community, social media content, and online purchase intention. The results of this study will facilitate policymakers and online marketers in devising UGC management policies and digital marketing strategies. The study’s results may also help online marketers, sellers, and brand representatives to understand how to enhance brand image and amplify customers’ online purchasing behavior.